(untitled) (CAHIERS MAGELLANES-NS, 2024)
Digital technology has delivered a revolutionary impact on every sector in the country. Government initiations and infrastructure for digital growth especially in the financial sector gained revolutionary changes in past decades with the introduction of digital financial services such as ATMS, POS Terminals, internet banking, E-wallets, mobile banking, payment apps, and many more. Accessibility to mobile phones and internet-related services to mass allowed many people to use digital services. Digital financial services give women an opportunity to use financial services at their fingertip and allow her to be financially literate, stable and independent so that she can overcome gender biases and inequality in financial terms. The primary objective of the research is to analyse the role of digital financial services on empowering rural women in her journey towards financial independency. So this study evaluates the influence of the digital revolution in the banking sector on rural women by concentrating on how the revolution in digital financial services changed their financial activity and empowered them. The study uses a quantitative survey questionnaire consisting of questions relating to access to financial services, decision-making, economic participation, and perception towards digital financial services to know how the digital revolution has empowered them. The present study is concentrated on rural women staying in the Bengaluru rural district of Karnataka state. The preliminary finding of the investigation shows that digital financial services such as ATMS and mobile payment apps such as Google Pay, Paytm, etc. have helped women to effortlessly do their transactions and save their time to stand in queue before banks to get cash for their requirements. It is also recognised that digital financial services have made them experience the empowerment in society; however, they perceive security concerns and a lack of confidence in digital banking services as hindrance to utilise the digital services. To bring light to the topic, the importance of this study lies in identifying the level of awareness and perception of rural women towards digital financial services, as this study tries to suggest policies to enhance digital financial education in rural women as empowerment is in educating the people on the issues and opportunity available to them. The government should leverage the technological changes to reach the last person in the country so that accessibility and usability of digital services will allow economic growth and empowerment of rural and unorganized sector.